Karakteristik Pola Perjalanan Pengguna Tunai BRT Trans Jogja - Aghisna, Alfin; Dewi, Diah Intan Kusumo (Teknik PWK (Perencanaan Wilayah Kota), 2023)
City residents need convenient, cheap, safe and easy transportation to meet their daily needs. Mandatory to use non-cash payments in using BRT transportation Policy is one of the steps that can help alleviate queuing problems that can help time efficiency. The policy of using non-cash payments in BRT transportation has been implemented in several cities in Indonesia. The use of cash payment instruments is still superior because currently it is still more common and easier to use, especially in the use of the Trans Jogja BRT. This study aims to determine the characteristics of payment system users based on their travel patterns in assisting policy makers in determining payment service policies in the Trans Jogja BRT. This research is quantitative by identifying the characteristics of user travel patterns through descriptive statistical analysis. BRT Trans Jogja cash payment users are users who come from DIY Province, use BRT Trans Jogja less than 3 times a week and are users 3-4 years old. Users usually walk to the bus stop which is less than 1 km and make payment transactions to officers with a waiting time of < 15 minutes. These users are users who must get cash payment services, so cash payments need to be increased through increased cash payment facilities.